Using insects against cancer - Bozdoğan, Hakan; Cuéllar-Cardozo, José Alejandro (Experimental Biology and Biotechnology, 2023)
In this work, the usage areas of some insect orders such as Hymenoptera, Coleoptera, Diptera, Lepidoptera, Orthoptera and Blattodea in oncological studies are discussed with some parameters.